Sociological Analysis of Branding of Professional Football League Players - Pashaie Sajjad; Piątkowska Monika; Hoseini Mir Davood; Dostimehr Ali; Jahanbakhsh Iraj (Sciendo, 2022)
The role of branding the sports performance of Iranian professional football League players was investigated by adopting a survey-based research strategy. Players with a history of competing in the Iranian Football League made up the statistical population for the study. 200 players were selected from this population as the study sample. The questionnaire data obtained were analyzed using IBM® SPSS® Amos TM 23 software. The validity and reliability of the questionnaires were acceptable and a good fit. The results showed that the structural equation model used is a strong theoretical model for studying the branding of Iranian League players, and that such branding has a significant positive effect on sports performance. Therefore, sports clubs need to understand the power of branding players to increase their athletic performance in sports expertise, competitive style and fair play. On the other hand, the most important aspect of branding is branding the whole club, rather than each product or player, since each individual product can benefit from the income belonging to the brand family of the club or organization. It is suggested that professional and strategic methods can help players and motivate them to acquire the necessary skills to grow branding.